KONSTRUKSI KAUSATIF ANALITIK DALAM BAHASA JAWA DAN BAHASA INDONESIA - Nurhayati, Tuty (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2018)
This study aims to reveal how the Javanese and Indonesia language is formed in the perspective of analytic causative construction. The analytic causative concept refers to the causative concept according to Comrie (1989). This research data is obtained from written sources. The markup method is applied in analyzing research data based on the issues discussed in this article. The results of this study indicate that the analytic causative construction in Javanese can be formed with the verb nggawe (make). Javanese analytic construction has a biclausal structure, as seen from their ability to take polarity and different modalities for verbs. While in causative analytic language can be formed with various verbs such as: make, cause, invite, enjoin, ask and make and have monoklausa structure.Keywords: Analytic causative, Javanese, Indonesian, method of marking